2012
DOI: 10.4329/wjr.v4.i4.135
|View full text |Cite
|
Sign up to set email alerts
|

Reliable clinical and sonographic findings in the diagnosis of abdominal wall endometriosis near cesarean section scar

Abstract: AIM:To highlight sonographic and clinical characteristics of scar endometrioma with special emphasis on size-related features�� METHODS: Thirty women (mean age 30��6 years, range 20-42 years) with 33 scar endometriomas (mean diameter 27��1 mm, range 7-60 mm) were consecutively studied by Sonography and Color �oppler examination prior to surgery�� Pathological examination was available in all cases�� RESULTS:The most frequent (24 of 33 nodules, 74%) sonographic B-mode aspect of endometrioma was that of an inhom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
3
24
2
14
Order By: Relevance
“…The sonographic appearance of abdominal wall endometrioma can be cystic, multicystic, mixed, or solid (12). The echo pattern may or may not correlate with the menstrual period, and sonographic findings are nonspecific (13). In our study, sonographic examination revealed these masses to be solid, hypoechoic lesions in the abdominal wall and to contain internal vascularity on CDUS.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The sonographic appearance of abdominal wall endometrioma can be cystic, multicystic, mixed, or solid (12). The echo pattern may or may not correlate with the menstrual period, and sonographic findings are nonspecific (13). In our study, sonographic examination revealed these masses to be solid, hypoechoic lesions in the abdominal wall and to contain internal vascularity on CDUS.…”
Section: Discussionmentioning
confidence: 69%
“…AWE cannot be distinguished from invasive abdominal masses by CT (12,14,17). Although, typically, MRI is suited best for defining the anatomy of the soft tissue mass and its surrounding structures, the signal characteristics and contrast enhancement pattern of AWE are not specific, and the true histological nature of the tumour or other soft-tissue masses often cannot be ascertained by imaging alone, with few exceptions (e.g., lipoma or haemorrhage) (13,18). However, MRI has become a useful tool in AWE to provide a roadmap for operations to determine the location and depth of infiltration in the surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Эндометриоз достаточно частое заболе-вание у женщин репродуктивного возраста, однако его локализация в области послеопе-рационного рубца (Эпр) относится к редким формам и в литературе имеются публикации по данной патологии в виде описания отдель-ных клинических наблюдений или небольших серий [1][2][3][4][5][6][7][8][9][10][11][12][13]. в большинстве случаев Эпр возникает после кесарева сечения и других гинекологических операций (гистерэктомии, удаления эндометриоидных кист яичника) [7,[11][12][13] и, тем не менее, в литературе опублико-ваны документированные наблюдения данно-го вида экстрагенитального эндометриоза по-сле хирургических операций (аппендэктомия, холецистэктомия, грыжесечение) [4,8,11].…”
Section: Introductionunclassified